7(x+5)-2x-40=-3(2x-9.4)+4

Simple and best practice solution for 7(x+5)-2x-40=-3(2x-9.4)+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x+5)-2x-40=-3(2x-9.4)+4 equation:


Simplifying
7(x + 5) + -2x + -40 = -3(2x + -9.4) + 4

Reorder the terms:
7(5 + x) + -2x + -40 = -3(2x + -9.4) + 4
(5 * 7 + x * 7) + -2x + -40 = -3(2x + -9.4) + 4
(35 + 7x) + -2x + -40 = -3(2x + -9.4) + 4

Reorder the terms:
35 + -40 + 7x + -2x = -3(2x + -9.4) + 4

Combine like terms: 35 + -40 = -5
-5 + 7x + -2x = -3(2x + -9.4) + 4

Combine like terms: 7x + -2x = 5x
-5 + 5x = -3(2x + -9.4) + 4

Reorder the terms:
-5 + 5x = -3(-9.4 + 2x) + 4
-5 + 5x = (-9.4 * -3 + 2x * -3) + 4
-5 + 5x = (28.2 + -6x) + 4

Reorder the terms:
-5 + 5x = 28.2 + 4 + -6x

Combine like terms: 28.2 + 4 = 32.2
-5 + 5x = 32.2 + -6x

Solving
-5 + 5x = 32.2 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-5 + 5x + 6x = 32.2 + -6x + 6x

Combine like terms: 5x + 6x = 11x
-5 + 11x = 32.2 + -6x + 6x

Combine like terms: -6x + 6x = 0
-5 + 11x = 32.2 + 0
-5 + 11x = 32.2

Add '5' to each side of the equation.
-5 + 5 + 11x = 32.2 + 5

Combine like terms: -5 + 5 = 0
0 + 11x = 32.2 + 5
11x = 32.2 + 5

Combine like terms: 32.2 + 5 = 37.2
11x = 37.2

Divide each side by '11'.
x = 3.381818182

Simplifying
x = 3.381818182

See similar equations:

| 9(n+6)=10 | | -11+p=-5 | | 0.04y=0.02-y | | 0=y^2-6y | | -.4f+2=.2f+11 | | 6x^3-x^2-5x=0 | | 90=1500*r*2 | | y=41/11(88)+128/11 | | 4x-6=3x+6 | | .25+x=-.58 | | 7(3x+6)=7-(x-2) | | 8(v+2)-4v=2(2v+1)-4 | | y=41/11(20)+128/11 | | -6m-6+8m=-5m-5+2m-1 | | y=41/11(18)+128/11 | | 3=4p+8-3p | | -30=5r | | (y-4)(3-7)=.25 | | 3c+5=2c+2 | | 67x-34+2=5 | | 8(v+2)-4v+7=8v+7 | | 3+(56+x)=34 | | 21j-12=14j+37 | | -6y+14+14y=32 | | 7=-d+13 | | -21.2=p-12.7 | | .333h-4(.666h-3)=.666h-6 | | 8-5n=-7 | | 18a^6-25a^5+8a^4=0 | | 4n+12=2 | | 4x-2/3=x+2 | | 4s-1=8-2a |

Equations solver categories